Activities and Achievements of Himachal Pradesh State Forest Corporation Limited - Gupta, D. P.; Verma, P. C. (Indian Forester, 1991)
Keeping in view scientific exploitation of forest produce and to eliminate middleman, Himachal Pradesh State Forest Corporation Limited was Incorporated on 25.3.1974 and started functioning from 1.4.1974. In the Initial stage, Corporation was given management of two rosin and turpentine factories but subsequently on the basis of good performance, most of the work related to forest produce such as timber and fuelwood extraction, resin tapping, harvesting of bamboos and khair and marketing were transferred to Corporation. The Corporation was also entrusted the work of timber supply for apple packing cases. With tbe efforts of the Corporation, some headway has been made to save fir, spruce and kail timber by using poplar and Eucalyptus timber for packing cases.